Construction of Recharge Well Project as an Effort to Prevent Flooding on Balai Street, Rawabangun Subdistrict, Taman Sari District, Pangkal Pinang City - Aswandi; Eka Naufal Daffa; Miranda; Erni Yusnita; M. Afdal Samsuddin (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2024)
Flooding in urban areas has become a serious issue, including in Jalan Balai, Rawabangun Subdistrict, Pangkalpinang, which frequently experiences inundation due to insufficient water infiltration and inadequate drainage systems. This study aims to analyze the effectiveness of infiltration wells in mitigating floods, assess their impact on the community, and evaluate their financial feasibility. The research employs a descriptive quantitative approach, utilizing primary and secondary data analysis. The study results indicate that the infiltration well construction project is feasible, with a positive NPV of Rp 142,743,495 (10%) and Rp 111,783,802 (15%), an IRR of 12.8%, a BCR of 2.06, and a payback period of 1.85 years. This construction is expected to reduce water inundation, enhance community mobility, and support environmental sustainability by preserving groundwater reserves. Additionally, the project provides a strategic solution to minimize flood risks and improve the quality of life for the local community. The study recommends regular maintenance of infiltration wells and public awareness campaigns to ensure their effectiveness.